Higher Education Students’ Dropout Intentions: Organizational And Profession/Career Factors - Campos, Sofia (2019)
Background: The promotion of students' academic success has been a growing concern for higher education institutions, a responsibility that should have an impact on the reduction of failure and dropout rates, as well as on the general improvement of the students’ training and on the development of their skills competencies and on the students’ graduation rates. Objectives: Our general objective was to identify the factors that interfere in the dropout intentions of the students who attend the Polytechnic Institute of Viseu. Specifically, we sought to identify socio-demographic variables, organizational and profession/career factors that may have an impact on higher education students’ dropout intentions and to analyze the relationship between them. Method: Quantitative, cross-sectional, descriptive and correlational study. A socio-demographic characterization questionnaire was applied to the students and the Brazilian “Reasons for Higher Education Dropout Scale” (M- ES; Ambiel, 2015) was also used. The sample is composed of 891 higher education students attending different organic units in a Polytechnic Institute. The elements of the sample were predominantly female (68.2%), with a mean age of 19.68 years (± 2.34 years), with a predominance of older students (≥20 years) (38.3%). Results: Our intention was to know whether or not gender will influence school dropout. It was possible to find out that male students consider the organizational dimension as an inherent element of school dropout, while female students indicate the profession/career dimension as the most important dimensions. It turns out that the 19-year-old students are those who reveal more reasons that can lead them to school dropout, especially in terms of organizational and relational dimensions. Conclusion: In view of these results, it is suggested that more measures should be implemented in order to contribute to the prevention / reduction of school dropout among higher education students. This strategy requires that the institution should be aware of the students' personal attitude, of their interest in learning, of their commitment and determination.